Pragmatism and democratic theory: the non-instrumental value of democracy (Leviathan (São Paulo), 2021)
The article discusses the current processes of democratic recession considering, on one hand, the minimalist interpretations in democratic theory, and, on the other, the pragmatist approach as developed by authors such as John Dewey, George Mead and Elizabeth Anderson. In view that authoritarian leaders have been eroding democracy through the institutions and enshrined rules of liberal democracy, it is questioned to what extent competitive perspectives – and a certain institutionalist political science – would allow us to criticize the dedemocratization undergoing in several national contexts. As an alternative, it will be presented the contribution of pragmatism to the rescue of the idea of democracy, which understands this regime beyond its materialization in institutional arrangements. It is argued that this position highlights the values attributed to democratic politics and characterizes it as a way of life based on a dialogic interaction that extends to different areas of social life. In this way, it would be possible to carry out both a critical diagnosis about the new authoritarianism and to think of ways to rescue democracy in its radical sense.